The effects of chronic endometritis on the pregnancy outcomes. (23rd October 2020) - Morimune, Aina; Kimura, Fuminori; Nakamura, Akiko; Kitazawa, Jun; Takashima, Akiko; Amano, Tsukuru; Kaku, Shoji; Moritani, Suzuko; Kushima, Ryoji; Murakami, Takashi
Abstract : Problem: Chronic endometritis (CE) influences the clinical outcomes of assisted reproductive technology. However, the effect of CE on the pregnancy outcome is still unknown. Method of study: A retrospective case‐control study was conducted in a single university. Subjects who conceived by in vitro fertilization within a year after a histological diagnosis of CE under 40 years of age from September 2013 to December 2017 were extracted. The rates of miscarriage, preterm birth, term birth, and live birth per pregnancy according to the presence or absence of CE were analyzed. A logistic regression analysis was performed for miscarriage, preterm birth, term birth, and live birth for eight explanatory variables of seven infertility factors and CE. Results: A total of 39 pregnancies in 38 subjects with non‐CE and 35 pregnancies in 32 subjects with CE were ultimately analyzed. The rates of miscarriage, preterm birth, term birth, and live birth per pregnancy were 12.8% and 40.0% ( P < .03), 2.6% and 14.3% ( P = .1), 84.6% and 45.7% ( P < .001) and 84.6% and 57.1% ( P < .03) in the Non‐CE and CE groups, respectively, although only the analysis for tem birth rate had sufficient power to exclude Type II error. In logistic analysis, CE was a factor affecting the objective variables of miscarriage, term birth, and live birth. Conclusions: The term birth rate among pregnancies decreased mainly due to an increase in miscarriages when CE was detected before pregnancy in patients treated with in vitro fertilization. A histopathological diagnosis of CE adversely affected the term birth rate per pregnancy.